The Causality between Indonesian Sharia Stock Index and Market Capitalization: Evidence from Indonesia - Fera Widyanata; Abdul Bashir (Jurnal Ekonomi dan Studi Pembangunan, 2020)
This study investigates the relationship between the sharia stock index and market capitalization in Indonesia for the period 2011-2019. This study uses secondary data, it is monthly time series data with 97 months observation period from May 2011 until March 2019. The analysis technique of this study is the granger causality test that is complemented by the impulse response and variance decomposition test. the findings of the study indicated that there was only a one-way causality relationship between the sharia stock index variable and market capitalization, which only the changes of market capitalization in the past affected the changes of the sharia stock trading value in the present but not vice versa.  The effect of market capitalization changes will be responded strongly by sharia stock in the second and third month, and then return to a new stable condition. Furthermore, the changes in the value of market capitalization provide a sizable and continuous contribution to the changes of sharia stock trading value